Eksploitasi Jasa Anak Menurut Undang-Undang ‎Nomor 23 Tahun 2002 dan Hukum Pidana Islam - Shofiyul Fuad Hakiky (Prodi Hukum Pidana Islam Fakultas Syari’ah dan Hukum Universitas Islam Negeri Sunan Ampel Surabaya, 2016)
Abstract: Exploitation to a child is an inhumane act. Although a ban on the exploitation of child’s services is legally mentioned in legislation, but it is different in reality. We can see some adult people take their babies to begging, singing under traffic light, even they are recruited as factory workers and others. It is because the exploiters of the children’s service are less fear or underestimate to the existing sanctions under the child protection legislation No. 23 of 2002. The criminal sanction against perpetrators of child exploitation as contained in Law No. 23 of 2002 section 83, 84, and 88 is considered less straight. On Islamic jurisprudence perspective, a child is in need of special attention. It can be in the form of guidance, education, and legal protection. Whatever is done by a child, it has not been subjected to the burden of law. So that even if the child was given a penalty, then the punishment should be an educational one, not to exceed the limit of a child’s ability. On the other hands, considering the mental and psychological effects of the child is quite important for his/her development in the future. Keywords: Exploitation, children’s services, law, Islamic criminal law. Abstrak: Eksploitasi anak merupakan tindakan yang tidak berperikemanusiaan. Meskipun larangan eksploitasi jasa anak ada dalam undang-undang, tetapi pada kenyataannya masih terjadi, contohnya; anak bayi yang diajak orang tuanya mengemis, mengamen di pingir perempatan lampu lalu lintas, buruh pabrik, dan lain-lain. Hal tersebut dikarenakan pelaku eksploitasi jasa anak kurang takut atau meremehkan sanksi yang ada dalam undang-undang perlindungan anak No.23 tahun 2002. Sanksi pidana terhadap pelaku eksploitasi jasa anak yang tercantum dalam Undang-undang No. 23 Tahun 2002 tentang Perlindungan Anak terletak pada pasal 83, 84, dan 88. Dalam pandangan fiqh anak-anak perlu mendapat perhatian khusus, berupa pembinaan, pendidikan, dan perlindungan hukum. Apapun yang dilakukan oleh anak-anak belum dikenai beban hukum, sehingga kalaupun anak itu diberikan sanksi, maka sanksinya harus bersifat pendidikan, tidak melampaui batas kemampuan anak, dan harus mempertimbangkan efeknya terhadap perkembangan jiwa anak. Kata Kunci: Eksploitasi, jasa, anak, undang-undang, Hukum pidana Islam.